Retired teachers of the ecuadorian magistery and its economic compensation issued in state bonds - Analuisa Aroca, Iván Alberto; Rodríguez Ulcuango, Olga Maritza; Delgado Rodríguez, Carlos Augusto (mktDESCUBRE, 2017)
The objective of the research is to analyze the economic compensation in bonds of the Ecuadorian state, received by teachers retired from the teachers of the provinces of Chimborazo, Pastaza and Bolivar, framed in resolution 003 and 018 of the Ministry of Finance. Under the quasi-experimental research method and retrospective source observation, the quantitative result of the negotiations conducted determined that in the year 2016, about 12.2 million dollars were depreciated of 44.5 million in nominal value, concluding a reduction in the economic compensation of the Retired when presenting a discount of 22% to the original market value, which generates uncertainty in the optimization of yield by selling the bond to place it in financial institutions, taking into account that the benefit and the immediacy of receiving the cash is personalized , But always highlighting the financial essence: “Money is worth more today than tomorrow.”